2021
DOI: 10.1039/d0fo02695f
|View full text |Cite
|
Sign up to set email alerts
|

Zanthoxylum alkylamides ameliorate protein metabolism in type 2 diabetes mellitus rats by regulating multiple signaling pathways

Abstract: Type 2 diabetes mellitus (T2DM) can easily induce insulin resistance (IR) in skeletal muscle, causing protein metabolism disorder and inflammation. The present study aimed to investigate whether Zanthoxylum alkylamides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…AMPK, mainly expressed in the liver and muscle, plays important roles in energy and carbohydrate metabolism . As reported, AMPK activation promotes the expression of glucose transporter proteins and glucose uptake and utilization, further improving energy metabolism and inhibiting insulin resistance . Hepatic AMPK activation is often accompanied by reduction in hepatic glucose production .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AMPK, mainly expressed in the liver and muscle, plays important roles in energy and carbohydrate metabolism . As reported, AMPK activation promotes the expression of glucose transporter proteins and glucose uptake and utilization, further improving energy metabolism and inhibiting insulin resistance . Hepatic AMPK activation is often accompanied by reduction in hepatic glucose production .…”
Section: Discussionmentioning
confidence: 97%
“…29 As reported, AMPK activation promotes the expression of glucose transporter proteins and glucose uptake and utilization, further improving energy metabolism and inhibiting insulin resistance. 30 Hepatic AMPK activation is often accompanied by reduction in hepatic glucose production. 31 This may be because of the AMPK-mediated suppression of hepatic gluconeogenesis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Multiple studies have revealed the role of Akt/mTOR signaling in regulating β-cell function (Leibowitz et al, 2009;Xie & Herbert, 2012;Yin et al, 2017). The Akt/mTOR pathway has been considered a target for T2DM therapy in recent years (Wei et al, 2021;Xu et al, 2021). the PI3K/Akt pathway in pulmonary arterial hypertension and regulated the proliferation and migration of pulmonary artery smooth muscle cells (Hu et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed the role of Akt/mTOR signaling in regulating β‐cell function (Leibowitz et al, 2009; Xie & Herbert, 2012; Yin et al, 2017). The Akt/mTOR pathway has been considered a target for T2DM therapy in recent years (Wei et al, 2021; Xu et al, 2021). Furthermore, studies have indicated that TRIM32 modulates the Akt/mTOR pathway in multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The weight of the mice was recorded every week. The preliminary studies of this project showed that the intragastric dose of 4~12 mg/kg·bw had an effect on lipids, blood glucose, and protein, among which 8 mg/kg·bw had a significant effect on lipid, sugar, and protein metabolism in mice [ 16 , 19 , 20 ]. Therefore, the intragastric dose in this study was based on the results of previous studies.…”
Section: Methodsmentioning
confidence: 99%